Insights from homozygous signatures of cervus nippon revealed genetic architecture for components of fitness - Goli, Rangasai Chandra; Mahar, Karan; Manohar, Peela Sai; Chishi, Kiyevi G; Prabhu, Immanual Gilwax; Choudhary, Sonu; Rathi, Pallavi; Chinnareddyvari, Chandana Sree; Haritha, Pala; Metta, Muralidhar; Shetkar, Mahantesh; Kumar, Amit; et al. (Mammalian genome, 2024)
This study investigates the genomic landscape of Sika deer populations, emphasizing the detection and characterization of runs of homozygosity (ROH) and their contribution towards components of fitness. Using 85,001 high-confidence SNPs, the investigation into ROH distribution unveiled nuanced patterns of autozygosity across individuals especially in 2 out of the 8 farms, exhibiting elevated ROH levels and mean genome coverage under ROH segments. The prevalence of shorter ROH segments (0.5-4 Mb) suggests historical relatedness and potential selective pressures within these populations. Intriguingly, despite observed variations in ROH profiles, the overall genomic inbreeding coefficient (F ROH ) remained relatively low across all farms, indicating a discernible degree of genetic exchange and effective mitigation of inbreeding within the studied Sika deer populations. Consensus ROH (cROH) were found to harbor genes for important functions viz., EGFLAM gene which is involved in the vision function of the eye, SKP2 gene which regulates cell cycle, CAPSL involved in adipogenesis, SPEF2 which is essential for sperm flagellar assembly, DCLK3 involved in the heat stress. This first ever study on ROH in Sika deer, to shed light on the adaptive role of genes in these homozygous regions. The insights garnered from this study have broader implications in the management of genetic diversity in this vulnerable species. Graphical abstract